Albutrepenonacog alfa (Idelvion®) for the treatment of Italian patients with hemophilia B: a budget impact model - Pradelli, Lorenzo; Villa, Sara; Castaman, Giancarlo (Farmeconomia. Health economics and therapeutic pathways, 2018)
BACKGROUND: Enhanced pharmacokinetic profile of albutrepenonacog alfa allows to prolong the interdose period in prophylaxis, maintaining higher trough level, and to reduce dosage needed for bleeding. This improvement could lead to a better efficiency of the hemophilia B treatment. OBJECTIVES: To estimate the impact of this new drug on the Italian National Health System (NHS). METHODS: A model was developed from the NHS perspective to assess the budget impact of treating severe hemophilia B with reimbursed recombinant factor IX over 3 years in Italy. Target population was based on data from the National Registry of Congenital Coagulopathies, which collects data from 54 Hemophilia Treatment Centers. Treatment options were: albutrepenonacog alfa (Idelvion®), eftrenonacog alfa (Alprolix®) and nonacog alfa (BeneFIX®). Annual bleeding rate, dose and infusions needed to treat an episode based on clinical trials data were considered. RESULTS: Mean costs per patient were calculated for prophylaxis and bleeding treatment by age groups. Applying age-specific costs to the expected new pattern of drugs utilization, the impact on the NHS budget was € 6 million of savings cumulated in 3 years. The model results most sensitive to drug dosages. Lower drug consumption in prophylaxis and reduced bleeding rate than the alternatives reduce expenditures. Main limitations of this analysis were the assumptions that all severe patients receive prophylaxis and the lack of consideration of positive effects of hemorrhagic complications reduction (with consequent lower need of physiotherapy/prosthetic substitution). CONCLUSIONS: The introduction of Idelvion® as therapeutic option for hemophilia B is expected to decrease pharmaceutical costs and improve patient’s quality of life due to less frequent infusions.